2013
DOI: 10.1007/s10620-013-2802-y
|View full text |Cite
|
Sign up to set email alerts
|

Hepatogenous Diabetes in Cirrhosis Is Related to Portal Pressure and Variceal Hemorrhage

Abstract: HD and IR have significant relationships with PHT and variceal hemorrhage. Postprandial hyperglycemia in particular had a significant relationship with variceal hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 27 publications
2
28
0
1
Order By: Relevance
“…Actually, investigators have suggested the limited linkage between portal pressure and IR. One theory is that a correlation between HOMA2-IR and HVPG was lost when only patients with clinically significant portal hypertension (HVPG > 10 mmHg) were considered 26, and the other suggestion is that high IR is related to high portal pressure though no correlation was found between IR (HOMA) and HVPG 27. A possible explanation may be a presence of spontaneous shunt formation, which diverts portal blood flow away from the liver, resulting in the reduction of portal pressure 28, and therefore may enhance the importance of the evaluation of physiological portal haemodynamics for the identification of potential IR and of the identification of collateral flow volume > 165 mL/min.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, investigators have suggested the limited linkage between portal pressure and IR. One theory is that a correlation between HOMA2-IR and HVPG was lost when only patients with clinically significant portal hypertension (HVPG > 10 mmHg) were considered 26, and the other suggestion is that high IR is related to high portal pressure though no correlation was found between IR (HOMA) and HVPG 27. A possible explanation may be a presence of spontaneous shunt formation, which diverts portal blood flow away from the liver, resulting in the reduction of portal pressure 28, and therefore may enhance the importance of the evaluation of physiological portal haemodynamics for the identification of potential IR and of the identification of collateral flow volume > 165 mL/min.…”
Section: Discussionmentioning
confidence: 99%
“…13 More recent single-centre surveys using current criteria for DM diagnosis 2 have shown that, based on fasting plasma glucose (FPG) levels, alone or associated with measurements of haemoglobin (Hb) A 1c , prevalence of DM in cirrhotic individuals is approximately 30%-40% (Table 1). In particular, Holstein et al 14 Jeon et al 17 of 34.4%. In addition, three studies in cirrhotic patients on the waiting list for OLT (including two surveys from our group) reported prevalence values of 41.7%, 18 27.2%, 19 and 30.7%, 20 respectively, for overt DM, and 16.6%, 18 3.4%, 19 and 10.3%, 20 respectively, for IFG.…”
Section: Epidemiologymentioning
confidence: 97%
“…Presence of DM was also shown to be associated with hepatic encephalopathy, possibly due to multiple mechanisms, as well as with acute liver failure . In addition, incidence rates of ascites, gastrointestinal haemorrhage, bacterial infections, and peritonitis were higher in diabetic than in non‐diabetic cirrhotic individuals. Finally, a large body of evidence indicates that risk of HCC is higher in cirrhotic subjects with DM than in those without …”
Section: Clinical Featuresmentioning
confidence: 98%
See 1 more Smart Citation
“…이뤄지고 있으며 (12)(13)(14)(15)(16)(17) Lactobacillus curvatus isolated from Kimchi; 2) Weissella viridescens isolated from Kimchi; 3) Lactobacillus plantarum isolated from Kimchi; 4) Leuconostoc lactis isolated from Kimchi; 5) Lactobacillus acidophilus isolated from Kimchi; 6) Lactobacillus sakei subsp. isolated from salt-fermented shrimp;…”
mentioning
confidence: 99%